Population dynamics of the potato cyst nematode, Globodera pallida, in relation to temperature, potato cultivar and nematicide application. (10th March 2019) - Kaczmarek, A. M.; Back, M.; Blok, V. C.
Abstract : The impact of increasing temperatures on the population dynamics of the soil‐dwelling nematode Globodera pallida, a persistent and economically important pest of potatoes, was investigated. The reproductive factor (final population⁄initial population) and length of life cycle were found to be temperature sensitive. Pot experiments performed over 4 months allowed comparison of the effect on development of G. pallida of two temperature regimes: an average temperature comparable to current field conditions (14.3 °C) and an average temperature above current field conditions (17.3 °C). A larger second generation of juveniles was observed at 17.3 °C compared to 14.3 °C. Multiplication of G. pallida at field sites in Shropshire and East Lothian (average soil temperatures of 15.5 and 14.1 °C, respectively, during potato cropping) was also examined. A quantitative PCR assay and visual examination of roots were used to monitor the dynamics of the G. pallida populations in both field sites at 4‐weekly intervals. Four cultivars, Desirée, Cara, Maris Piper and Estima, were grown with and without nematicide treatments. Nematicide treatments suppressed population increases at both sites. Females were observed on the roots of cvs Cara and Desirée at the end of the growing season in Shropshire, but not at East Lothian, and are likely to represent a second generation.